Inflamassomos NLRC4 E NLRP3 na Doença Periodontal Experimental Induzida por Aggregatibacter Actinomycetemcomitans - Rocha, Fernanda Regina Godoy [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Inflammasomes are multi-protein complexes that can amplify the inflammatory signal in situations involving host-microbial interactions and host tissue destruction, such as chronic periodontal disease. There is a relative scarcity of information on the role of NLRC4 and NLRP3 inflammasomes in periodontal disease. In this study, we used a model of bacteria-initiated periodontal disease in WT, Ipaf-knockout (Ipaf-KO), Caspase 1-knockout (Casp1-KO) and NLRP3-knockout (NLRP3-KO) mice to describe the effect of those inflammasomes on inflammation and alveolar bone resorption. Heat-killed Aggregatibacter actinomycetemcomitans (Aa) were injected in the gingival tissues on the palatal aspect adjacent to first molars of wild-type (WT), Ipaf-KO, Casp1-KO and NLRP3-KO mice, and control animals received the suspension vehicle (PBS). Severity of bone resorption was quantitated by μCT analysis. Inflammation was assessed by immunofluorescence, verifying the presence and intensity of a pan-leukocyte (CD45) and a neutrophil (Ly6G) markers. Osteoclast number was determined by TRAP and gene expression of RANKL, MMP-13, TNF-a, IL-6 and IL-10 in the gingival tissues was evaluated by RT-qPCR. In the first publication, μCT analysis showed a significantly greater inflammatory bone resorption in Ipaf-KO mice; however there was no difference between WT and Ipaf-KO on osteoclast numbers of inflammatory infiltrate. Expression of candidate genes was also similarly increased by the induction of experimental periodontal disease, except for the expression of TNF-alpha and IL-10, which was already significantly higher in the gingival tissues of Ipaf-KO mice in the absence of experimental periodontal disease. We conclude that NLRC4 inflammasome has a protective role on inflammatory bone resorption in this experimental model. In the second publication we observed that severity of bone resorption was not affected by the lack of NLRP3 inflammasome, but it was reduced in Casp1-KO mice. Interestingly, the attenuation of alveolar bone resorption in Casp1-KO mice was accompanied by increase on the number of osteoclasts, whereas there were no significant changes on the inflammatory infiltrate or expression of candidate genes. The conclusion was that NLPR3 inflammasome does not play a significant role in induced inflammation and bone resorption and caspase-1 has a pro-resorptive role in these conditions.

Inflamassomos são complexos multi protéicos capazes de amplificar o sinal inflamatório em condições de interações microbiota-hospedeiro e destruição tecidual, como a doença periodontal crônica. Devido à escassez de informações sobre o papel dos inflamassomos NLRC4 e NLRP3 na doença periodontal, utilizamos neste estudo um modelo de doença periodontal induzida por bactérias em camundongos WT, Ipafknockout (Ipaf-KO), Caspase 1-knockout (Casp1-KO) e NLRP3-knockout (NLRP3-KO) para descrever o efeito destes na inflamação e reabsorção óssea alveolar. Aggregatibacter actinomycetemcomitans (Aa) inativadas pelo calor foram injetadas nos tecidos gengivais palatais adjacentes aos primeiros molares dos camundongos normais e knockout, e os grupos controle receberam o mesmo volume do veículo de suspensão (PBS). A severidade da reabsorção óssea foi quantificada por análise de μCT. A inflamação foi avaliada por imunofluorescência, verificando-se presença e intensidade da coloração por marcadores de leucócitos (CD45) e neutrófilos (Ly6G). O número de osteoclastos foi determinado por TRAP e a expressão gênica de RANKL, MMP-13, TNF-a, IL-6 e IL-10 nos tecidos gengivais avaliada por RT-qPCR. A publicação 1 mostra uma reabsorção óssea inflamatória significativamente maior nos camundongos Ipaf-KO, sem diferenças, porém, no número de osteoclastos entre WT e Ipaf-KO. A expressão dos genes-alvo aumentou com a indução da doença periodontal, exceto de TNFa e IL-10, que foram altas nos animais Ipaf-KO mesmo em ausência da doença periodontal, podendo-se concluir que o inflamassomo NLRC4 teve um papel protetor na reabsorção óssea inflamatória neste modelo experimental. Na publicação 2 observamos que a severidade da reabsorção óssea não foi afetada pela ausência do inflamassomo NLRP3, mas foi significantemente reduzida nos camundongos Casp1-KO, sendo acompanhada nestes por um aumento significante no número de osteoclastos. Não houve, no entanto, diferenças no infiltrado inflamatório ou na expressão dos genes-alvo, concluindo-se que NLRP3 não teve papel significante na inflamação e reabsorção óssea, e caspase-1 contribuiu para a reabsorção óssea nas condições deste estudo.
NLRC4 and NLRP3 inflammasome in periodontal disease induced by Aggregatibacter actinomycetemcomitans
Keywords: Doença periodontal; Inflamação; Inflamassomos; Imunidade inata; Aggregatibacter actinomycetemcomitans; Periodontal disease; Inflammation; Inflammasome; Innate immunity; Aggregatibacter actinomycetemcomitans